Effects of Urban Illumination on Insect Populations: AI-powered Insights into Environmental Challenges and Solutions - Dey, Sayon; Mahato, Nityanando; Chakraborty, Gourab; Debnath, Shouvik (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Artificial urban lighting seriously disrupts insect populations, creating a cascade effect on ecosystems and biodiversity. This research explores the many ecological challenges presented by urban lighting in terms of how it influences the behavior, physiology, and population dynamics of insects. Urban lighting changes behavioral patterns such as foraging, mating, and navigation, thereby affecting nocturnal activity and vulnerability to predators. This light disrupts insect circadian rhythms physiologically, impairs hormonal regulation, and affects their reproductive success. That jeopardizes their survival and fitness as a population while having adverse population dynamics in abundance and diversity decline that ripple down the food web, ultimately destabilizing ecosystems. Using AI approaches driven by data, the study seeks to understand, predict, and mitigate these effects. Advanced pattern recognition and risk modeling become facilitated with the aid of AI tools in adaptive lighting systems with the potential for reduced harm to the environment. The potential in creating sustainable solutions to urban lighting with regard to ecological integrity alongside human needs, this work thus sets forth a new dimension for such issues as calls for inter-disciplinary cooperation by highlighting the pressing nature of technological innovation into ecological understanding. Through the presentation of a comparative analysis of current mitigation strategies, we are able to identify gaps and suggest future directions for urban ecological management. These include biodiversity-sensitive lighting designs, integration of AI-based monitoring systems, and policy frameworks that prioritize ecosystem health alongside urban development.